2014
DOI: 10.1016/j.yjmcc.2014.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Thin filament incorporation of an engineered cardiac troponin C variant (L48Q) enhances contractility in intact cardiomyocytes from healthy and infarcted hearts

Abstract: Many current pharmaceutical therapies for systolic heart failure target intracellular [Ca2+] ([Ca2+]i) metabolism, or cardiac troponin C (cTnC) on thin filaments, and can have significant side-effects, including arrhythmias or adverse effects on diastolic function. In this study, we tested the feasibility of directly increasing the Ca2+ binding properties of cTnC to enhance contraction independent of [Ca2+]i in intact cardiomyocytes from healthy and myocardial infarcted (MI) hearts. Specifically, cardiac thin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 58 publications
2
29
0
Order By: Relevance
“…In myocyte contractile assays, L48Q cTnC significantly increased cellular fractional shortening in the absence of changes in Ca 2+ transient amplitude ( data not shown ), as previously reported (Feest et al, 2014). Acute expression of I61Q cTnC caused a modest reduction in fractional shortening with no changes in Ca 2+ transient amplitude reflecting the decreased sensitivity of the myofilaments to Ca 2+ ( data not shown ).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…In myocyte contractile assays, L48Q cTnC significantly increased cellular fractional shortening in the absence of changes in Ca 2+ transient amplitude ( data not shown ), as previously reported (Feest et al, 2014). Acute expression of I61Q cTnC caused a modest reduction in fractional shortening with no changes in Ca 2+ transient amplitude reflecting the decreased sensitivity of the myofilaments to Ca 2+ ( data not shown ).…”
Section: Resultssupporting
confidence: 88%
“…We also used mutant cTnCs because they represent the proximal Ca 2+ binding element of the sarcomere, hence allowing for a more direct modulation of the Ca 2+ -tension relationship without potential confounding effects. The L48Q and I61Q variants used here have been rigorously quantified for their effects on tension and Ca 2+ handling dynamics (Kreutziger et al, 2011; Parvatiyar et al, 2010; Tikunova and Davis, 2004; Wang et al, 2012; Feest et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Based on the current computational models, we and others have designed engineered cTnC variants with altered Ca 2+ binding affinities (to cTn) and demonstrated that those variants alter the contractile function in cardiomyocytes and correct or prevent disease-related aberrant Ca 2+ binding and contractile function [163, 187, 188, 203-209]. These studies also provide important implications with respect to the design of Ca 2+ sensitizing or desensitizing small molecules or drugs.…”
Section: Summary and Future Directionsmentioning
confidence: 85%
“…To evaluate the therapeutic potential of this delivery system, cardiomyocytes isolated from infarcted adult rat hearts were transduced. Contractility of the treated infarcted cardiomyocytes was significantly improved compared to untreated infarct cells, with the magnitude and rate of contraction restored to levels comparable to healthy (uninfarcted) cardiomyocytes(38). …”
Section: Translational Medicine Challenge: Developing a Gene-deliverymentioning
confidence: 94%